2012
DOI: 10.1161/circulationaha.112.103234
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Healthy Diet and Risk of Cardiovascular Disease Among Patients on Drug Therapies for Secondary Prevention

Abstract: Background-Diet quality is strongly related to cardiovascular disease (CVD) incidence, but little is known about its impact on CVD events in older people at high risk of CVD and receiving effective drugs for secondary prevention. This study assessed the association between diet quality and CVD events in a large population of subjects from 40 countries with CVD or diabetes mellitus with end-organ damage receiving proven medications. Methods and Results-Overall, 31 546 women and men 66.5Ϯ6.2 years of age enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
119
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(127 citation statements)
references
References 31 publications
(27 reference statements)
3
119
0
5
Order By: Relevance
“…Population-based epidemiological studies have stressed the important role of diet and lifestyle in the emergence of many degenerative chronic diseases, such as cancers and cardiovascular diseases, in both developed and developing countries [1]. If a global health goal is to increase the amounts of vitamins, minerals or phytonutrients consumed in the diet, then a sensible approach is to further enhance the nutritional content of highly consumed crops.…”
Section: Introductionmentioning
confidence: 99%
“…Population-based epidemiological studies have stressed the important role of diet and lifestyle in the emergence of many degenerative chronic diseases, such as cancers and cardiovascular diseases, in both developed and developing countries [1]. If a global health goal is to increase the amounts of vitamins, minerals or phytonutrients consumed in the diet, then a sensible approach is to further enhance the nutritional content of highly consumed crops.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with overt CHD and/or with diabetes mellitus are at an increased risk of cardiovascular events and dying from CHD. Lifestyle interventions, such as regular exercise, a healthy diet, weight loss, and smoking cessation, reduce the risk of adverse cardiovascular events (2)(3)(4). Controlling other risk factors, such as diabetes, arterial hypertension and hyperlipidemia, with pharmacotherapy also contributes to risk reduction (5).…”
mentioning
confidence: 99%
“…Health professional's advice to individuals to improve their diet quality would substantially reduce CVD recurrence beyond drug therapy alone and save lives globally. 13 A study revealed that additional support in modifying lifestyles is useful in the reduction of cardiovascular disease risk. Change in individual risk factors: blood pressure, lipid profile, weight, body mass index, waist circumference, smoking, diabetes has been measured in the study.…”
mentioning
confidence: 99%
“…A high-risk dietary pattern was seen to be significantly more in the younger age group and the literate group. 13,14 It has been demonstrated that physical activity reduces risk of CVD. 15 Most of the (80%) of global deaths related to CVD occur in low-and middle-income nations, which cover most countries in Asia.…”
mentioning
confidence: 99%